New Holistic Conceptual Framework for the Assessment of the Performance of Photocatalytic Pavement - Jimenez-Relinque, Eva; Rubiano, Francisco; Hingorani, Ramon; Grande, Maria; Castillo, Angel; Nevshupa, Roman; Castellote, Marta (Frontiers in Chemistry, 2020)
Despite serious health and environmental burdens associated with air pollution by NOx, the emission ceilings have been systematically exceeded in big European cities for several years. Photocatalytic technology can be an efficient solution for the removal of chemical air pollutants. Because diesel engine exhaust is the main source of NOx emissions, the application of a photocatalyst onto road pavement appears to be an effective NOx abatement method due to the large surface area, proximity to the emission source, and relatively good solar irradiance. Several laboratory-scale studies provided evidence demonstrating that most harmful contaminants can be readily mineralized. Furthermore, several projects were aiming to scale up this technology to pilot and real scales. Although the photocatalytic performances of selected materials in real urban environments were determined in some of these studies, the data are not conclusive for evaluating the overall performance because other material characteristics relevant to their functionality were not assessed. The lack of conformity criteria suitable for the evaluation of the overall performance of photocatalytic pavement under real operational conditions has generated skepticism and mistrust among public authorities and relevant stakeholders, which constrains the widespread implementation of this promising technology. In this context, the project LIFE–Photoscaling was focused on developing a new holistic conceptual framework to assess the photocatalytic pavement performance using the decision tool “Photoscaling Decision Maker” based on a set of quantitative indicators. For this purpose, a large volume of data obtained for 10 types of photocatalytic pavement materials was systemized on both the laboratory and pilot plant scales and three main indicators were defined: (1) photocatalytic performance effectiveness, (2) intrinsic performance, and (3) undesired secondary effects. Each top-level indicator includes several low-level subindicators associated with specific material characteristics. Finally, the ranges of the main indicators and subindicators and methods for their assessment were determined. These methods include standard, adopted, and original characterization techniques, which were selected based on the criteria such as simplicity, cost- and time-effectiveness, and relevance regarding the operational conditions.